Aplikasi Pencarian Dan Pemesanan Lapangan Bulutangkis Berbasis Web Di Kota Palopo - Faldi (Jurnal Publikasi Teknik Informatika, 2024)
Field search and booking applications are important tools to support the management of information and administration given the rapid development of technology (gadgets) today, for this reason research and development of field search and booking applications with a case study of badminton courts in Palopo city. The method used in this research is a method that produces new products from the results of the research itself, namely R&D or research and development with the Waterfall development model. The results of this study found that: (1) Based on the results of designing a web-based badminton court search and booking application that was built, it can facilitate the community in the process of searching and booking badminton courts. (2) Based on the results of the implementation carried out that the web-based badminton court search and booking application can be applied and used by the community, and the badminton court admin.